0
$\begingroup$

Let $\alpha = (\alpha_{1},\dots, \alpha_{n}) \text{ and } \beta = (\beta_{1},\dots, \beta_{n}) \in \mathbb{N}^{n}$ be two vectors of positive integers, and assume that $\beta_{i} \le \alpha_{i}$ for all $1\le i \le n$. As usual, let $\alpha ! = (\alpha_{1} !) \cdots (\alpha_{n}!)$ and $$\binom{\alpha}{\beta} = \frac{\alpha!}{\beta! (\alpha-\beta)!}.$$ We set $\vert \alpha \vert = \alpha_{1} + \dots + \alpha_{n} $. My question: Is it true that $$ \binom{\alpha}{\beta} \le \binom{\vert \alpha \vert }{\vert \beta \vert} $$

$\endgroup$
0
$\begingroup$

The inequality is true, and in fact it's rather simple to proof it. Observe that $\binom{\alpha}{\beta} = \prod_{i=1}^{n} \binom{\alpha_{i}}{\beta_{i}}$. The binomial coefficient $\binom{\alpha_{i}}{\beta_{i}}$ is the coefficient of $x^{\beta_{i}}$ in $(1+ x)^{\alpha_{i}}$, while $\binom{\vert \alpha \vert }{\vert\beta \vert}$ is the coefficient of $x^{\vert\beta\vert}$ in $(1+x)^{\vert \alpha \vert}$. The coefficient $\binom{\vert \alpha \vert }{\vert \beta \vert}$ of $x^{\vert \beta \vert }$ in $\prod_{i=1}^{n} (1+x)^{\alpha_{i}}$ is the sum of different products of monomial coefficients which contains $\prod_{i=1}^{n} \binom{\alpha_{i}}{\beta_{i}}$ as summand, and hence the desired inequality follows.

$\endgroup$
  • $\begingroup$ Is this Q/A thing done just to get a badge? $\endgroup$ – Nikunj Apr 1 '16 at 13:54
  • $\begingroup$ No, I just did not see the trivial answer yesterday. $\endgroup$ – Sebastian Apr 1 '16 at 14:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.